An approximation of linear evolution equation with stochastic partial derivative in Sobolev space - Osu, B.O.; Amadi*, I.U.; Davies‡, I. (International Journal of Mathematical Analysis and Modelling, 2023)
In this paper, the existence and uniqueness of classical solution of stochastic elliptic Partial Differential Equation was considered. The analytical approach of weak solutions is presented in details which has enough financial implications in time-varying investments. Finally, the computations were basically on invocation of ellipticity; which gave analytical estimates from the structural algebraic ellipticity assumption in Sobolev space.